We have the following system of equations:
![\begin{gathered} 3x+y=4 \\ 2x+y=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jo1auznhby2e0sqavkhsiynyqc8rksfzjv.png)
The linear combintation method is a process of adding two algebraic equations so that one od the variables is eliminated.
In this regard, by multiplying the second equation by -1, we obtain an equivalent system of equations:
![\begin{gathered} 3x+y=4 \\ -2x-y=-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1c93wpc444up0v0i5wf2a7d18rwml239qv.png)
Then, by adding both equations, we can eliminate the variable y, that is,
![\begin{gathered} 3x-2x+y-y=4-5 \\ \text{which gives} \\ x=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vog6ng1iq1le55j5mgtoivdhe4bpa53tcr.png)
Once we know the result for x, we can substitute its values into one of the orginal equations. Then, if we substitute x=-1 into the first equation, we have
![3(-1)+y=4](https://img.qammunity.org/2023/formulas/mathematics/college/w3c9l6jcz0yawiahfqdckb6w53jdvvwdj8.png)
which gives
![\begin{gathered} -3+y=4 \\ \text{then} \\ y=7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7i4v02spc8avgiz4qp1zkhr056zisqbwk9.png)
Therefore, the solution is ( -1, 7), which corresponds to the last option.